The robo-pigeon based on the multiple brain regions synchronization implanted microelectrodes. Issue 4 (3rd July 2016) - Huai, Rui-tuo; Yang, Jun-qing; Wang, Hui
ABSTRACT: Almost all multichannel microelectrodes are only applied to the same nucleus. The multiple brain regions synchronization implanted microelectrodes can be implanted in the several brain regions at the same time, when used in the robo-animal, which can reduce the operation process, shorten animals operation time. Due to electrode position relatively fixed, errors caused by each separately implanted electrode were reduced and the animal control effect was greatly increased compared to the original electrodes. The electrode fixed time was also extended. This microelectrode provided beneficial reference function for the study of the free state of small animals in different brain regions.